Edukasi Seksual dalam Pernikahan: Pandangan Syekh At-Tihami dalam Kitab Qurrah Al-Uyun - Affandy, Arif; Ardiansyah, Ardiansyah; Mutiara, Dwi Utamika (Universitas Semarang, 2023)
This research aims to explore the significant role of sexual education in preventing divorce within the context of Islamic marriages. Through the analysis of Syaikh Abu Muhammad At-Tihami's primary source,